The Implementation of PSBB during the Covid-19 through Online Media News Text: A Critical Discourse Analysis - Retna Isti Pratiwi; Teguh Setiawan (Budapest International Research and Critics University, 2021)
Online media has a crucial role in the news reporting during the pandemic. Various case issues and changes in people's behavior are easily accessible through online news. This study aims to explain how the structure of the text is displayed in news texts about the implementation of PSBB or social mobility control at the closing ceremony of McDonald's. The research method used is a qualitative method with the technique of critical discourse analysis of the Teun A. Van Dijk model which includes 3 dimensions, namely the dimensions of text, social cognition and social context. The data are in the form of online news published in three different media, namely kompas.com, tempo.com and detik.com which were issued in May 2020 with the main theme